2021
DOI: 10.1021/jacs.1c03375
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Nanoscale Cobalt Oxide Catalysts for the Oxygen Evolution Reaction: Maximum Performance, Minimum Effort

Abstract: The oxygen evolution reaction (OER) is a key bottleneck step of artificial photosynthesis and an essential topic in renewable energy research. Therefore, stable, efficient, and economical water oxidation catalysts (WOCs) are in high demand and cobalt-based nanomaterials are promising targets. Herein, we tackle two key open questions after decades of research into cobaltassisted visible-light-driven water oxidation: What makes simple cobalt-based precipitates so highly activeand to what extent do we need Co-WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 89 publications
(138 reference statements)
1
44
0
Order By: Relevance
“…In the electro‐conversion process, the crystal phases of cobalt sulfides were maintained well (Figure S9), whereas the surface of the nanorods became much rougher after CV activation, as reflected by the SEM images in Figures 2a and S10. Transmission electron microscope (TEM) images indicate the amorphous CoOOH nanosheet layers are coated on the surface of CoS α (Figure 2b and S11), which are consistent with previous reports [13–17] . The high annular scanning TEM (HAADF‐STEM) image and corresponding elemental mappings of Co 9 S 8 after CV activation display the surface distribution of O and internal distribution of S, further suggesting the formation of CoOOH/Co 9 S 8 (Figure 2c).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the electro‐conversion process, the crystal phases of cobalt sulfides were maintained well (Figure S9), whereas the surface of the nanorods became much rougher after CV activation, as reflected by the SEM images in Figures 2a and S10. Transmission electron microscope (TEM) images indicate the amorphous CoOOH nanosheet layers are coated on the surface of CoS α (Figure 2b and S11), which are consistent with previous reports [13–17] . The high annular scanning TEM (HAADF‐STEM) image and corresponding elemental mappings of Co 9 S 8 after CV activation display the surface distribution of O and internal distribution of S, further suggesting the formation of CoOOH/Co 9 S 8 (Figure 2c).…”
Section: Resultssupporting
confidence: 88%
“…The X‐ray diffraction (XRD) pattern of CoO 2 shown in Figure S28b agrees well with the simulated CoO 2 . As shown in Figure S28c, the Raman bands located at 448 cm −1 and 572 cm −1 can be observed, which can be attributable to Co 3+ and Co 4+ , respectively [3, 17, 22, 35] . Figure 4c and Figure S29 show the Raman spectra of Co 9 S 8 and different cobalt sulfide catalysts recorded at 10 mV intervals in the potential range of 1.3–1.5 V, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…32 The resulting high dissolved metals concentrations pose challenges for systems-level design. 33 Other catalysts based on first-row transition metals such as Ni and Mn have provided comparable OER activity, 34 although high overpotentials in near-neutral conditions and other systems-level considerations have driven the community's focus on either strong alkaline or strong acidic electrolytes, which we compare and contrast herein.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Briefly, cobalt-based catalysts are among the most active catalysts when electrodeposited from electrolytes containing phosphate, methylphosphonate, or borate, at pH from 7 to 9.2 to form the Co–Pi, Co–MePi, and Co–Bi OER catalyst families. , Detailed investigations have shown that operational stability of these catalysts results from a “self-healing” process in which dissolved Co species are redeposited from the electrolyte . The resulting high dissolved metals concentrations pose challenges for systems-level design . Other catalysts based on first-row transition metals such as Ni and Mn have provided comparable OER activity, although high overpotentials in near-neutral conditions and other systems-level considerations have driven the community’s focus on either strong alkaline or strong acidic electrolytes, which we compare and contrast herein.…”
Section: Resultsmentioning
confidence: 99%
“…Heteropolyoxometalates (HPOMs) are unique and extensively explored subsets of polyoxometalates (POMs), which exhibit many kinds of structural versatility and offer potential physicochemical applications in catalysis, multifunctional materials, medicine, magnetism, nanotechnology, and so on. [1][2][3][4][5][6] It is noteworthy that the redox-active heteroanion TeO 3 2− as a template plays an important role in the self-assembly process of HPOMs. Since the first tellurium-containing polyoxoanion [TeMo 6 O 24 ] 6− was reported by Evans in 1948, 7 many other tellurium-containing polyoxoanions have been continuously discovered.…”
mentioning
confidence: 99%